BAHAN ANTI NYAMUK (Mosquito repellent) dari AKAR TUBA (Derris elliptica (Roxb.) Benth) (Material Mosquito Repellent of Tuba Root (Derris elliptica (Roxb.) Benth) - Miduk Sihombing; Yunus Afifuddin; Luthfi Hakim (Peronema Forestry Science Journal, 2013)
The use of chemicals to control insects such as mosquitoes can have a negative impact on the environment and humans. The use of natural ingredients that are toxic and environmentally friendly like tuba plant (Derris elliptica (Roxb.) Benth) is one solution that is expected to be used as an alternative ingredient for protection against insects. This study research to determine the exact manner and evaluate extractive toxicity tuba root extract (Derris elliptica (Roxb). Benth) as an mosquito repellent by examining the effects of tuba root methanol extract and tuba  root chloroform extract  with different concentrations (0%, 2%, 4%, and 6%) on mortality and the mortality rate of mosquitoes. The results showed that there was a very significant effect of extract of tuba root against mosquito death. Tuba root with a concentration  6% is considered the most effective for killing 50% of mosquitoes. The results indicate that the tuba roots chloroform extract has its toxicity and  very high potential to be developed into an mosquito repellent. Keywords: Derris elliptica (Roxb.) Benth, tuba root, mosquito repellent, toxicity, mortality.